GALAMSEY'S GRIP: UNRAVELLING THE IMPACT OF ILLEGAL SMALL-SCALE MINING ON COCOA FARMING AND LIVELIHOODS - Appiah, Sylvia Kyerewaa; Osei, Collins; Amankwah, Kwadwo; Tham-Agyekum, Enoch Kwame; Bakang, John-Eudes Andivi; Ankuyi, Fred (Agricultural Socio-Economics Journal, 2024)
The encroachment of small-scale mining (galamsey) on fertile lands poses a significant threat to cocoa cultivation, affecting farmers' livelihoods and raising concerns about environmental sustainability. This study addresses the complex interaction between small-scale mining and cocoa farming. Conducted in the Bosome Freho district, Ashanti Region, the study employs a quantitative research design, utilizing a survey method with 316 cocoa farmers affected by galamsey. Descriptive statistics, including frequency and percentages, are applied to analyze data. Factors driving cocoa farmers to participate in galamsey include perceived profitability, low cocoa yields, high maintenance costs, and reduced cocoa prices. The perceived impact of galamsey on livelihood outcomes reveals concerns about environmental degradation, reduced farm output, soil fertility decline, and health and safety risks. Livelihood strategies employed include on-farm practices like intercropping and livestock rearing. Galamsey poses multifaceted challenges to cocoa farmers, affecting not only their livelihoods but also the environment and socioeconomic activities. The study highlights the need for comprehensive policies addressing the complex interplay between mining and agriculture, safeguarding environmental sustainability and farmers' well-being. The findings inform policymakers of the urgent need for stricter regulations, environmental safeguards, and diversified livelihood options for cocoa farmers.